2018
DOI: 10.5897/ajbr2017.0925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional, anti-nutritional and some biochemical studies on Pleurotus squarrosulus (Mont.) singer using rats

Abstract: Evaluation of nutritional, anti-nutritional and some biochemical studies on Pleurotus squarrosulus (Mont.) Singer using rats was undertaken with standard methods. Results of nutritional contents such as proximate composition revealed moisture (11.67%), crude protein (21.31%) and total carbohydrate (51.58%). Vitamin composition showed the presence of vitamins A (0.17 mg/kg), B2 (0.62 mg/kg), B3 (0.45 mg/kg), B6 (0.84 mg/kg), and D (0.82 mg/kg). Important minerals such as potassium (20.75 mg/100 g), calcium (41.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
2
19
2
Order By: Relevance
“…Luteinizing hormone (LH) is one the gonadotropins that stimulate the gonads both in testes of male and ovaries of female [39,40]. Luteinizing hormone stimulates the synthesis as well as the secretion of testosterone with the help of its receptors that bind to leydig cells [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Luteinizing hormone (LH) is one the gonadotropins that stimulate the gonads both in testes of male and ovaries of female [39,40]. Luteinizing hormone stimulates the synthesis as well as the secretion of testosterone with the help of its receptors that bind to leydig cells [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of haematological parameters can be used to determine the extent of deleterious effect of foreign compounds in the body (Mohammed et al, 2009;Duru et al, 2012b;Duru et al, 2018). Both plant extracts and free radical from alloxan, on the blood constituents of an animal are amongst the foreign compounds (Mohammed et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such plants are known as medicinal plants and are the main source of organic compounds such as polyphenols, tannins, alkaloids, carbohydrates, terpenoids, steroids, flavonoids and etcetera (Marles and Farnsworth, 1995). These compounds are collectively addressed as phytochemicals (Marles and Farnsworth, 1995;Amadi et al, 2012;Duru et al, 2018) and represent a source for the discovery and development of new types of antidiabetic molecules (Firdous, 2014). Nawrot et al (2003) and Agomuo et al, (2017) noted that natural compounds found in plants or their synthetic forms are the basis of modern pharmacopeia.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have reported evaluations on medicinal plants and their products in relation to the body [5][6][7][8][9]. Different studies have authenticated the potency of so many medicinal plants against different disease conditions [1,3,[10][11][12][13][14][15][16][17][18][19][20]. It has been reported that natural compounds found in plants or their synthetic forms are the basis of modern pharmacopeia [21][22].…”
Section: Introductionmentioning
confidence: 99%